Innovation of Ideological and Political Education Based on Artificial Intelligence Technology with Wireless Network - Tang, Chuanwen (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: To apply artificial intelligence technology to ideological and political education in colleges and universities, as well as to combine artificial intelligence technology with ideological and political education in colleges and universities, it is necessary that wireless networks have complete coverage. OBJECTIVES: How can ideological and political education in universities and colleges be merged with artificial intelligence? How can artificial intelligence be used to support progressive political education at the college level? Starting with these issues, this paper will focus on the development of ideological and political education in colleges and universities as its main research question and refer to artificial intelligence technology as a method of ideological and political education in colleges and universities supported by wireless networks. METHODS: By examining the characteristics of artificial intelligence and ideological education in colleges and universities, and combining the poor immediacy and weak timeliness of information dissemination, as well as the low degree of identification of student groups with the theoretical courses of ideological education in the field of ideological education under the view of artificial intelligence, to explore the path of innovation of ideological education, RESULTS: In order to adapt to the demands of AI technology and improve people’s capacity to use AI learning software, we need start with educators and educated individuals. Additionally, the government should encourage the development of artificial intelligence technologies financially and technically. Finally, it examines how civic education in colleges and universities could be improved through the use of artificial intelligence. This would allow civic education to benefit from the advantages of AI technology. CONCLUSION: In order to support the positive and healthy development of political education courses in colleges and universities across the nation, this paper encourages the creation of concepts and methods for teaching politics in higher education institutions.